Continuous Synthesis of Device-Grade Semiconducting Polymers in Droplet-Based Microreactors - Bannock,JH; Krishnadasan,SH; Nightingale,AM; Yau,CP; Khaw,K; Burkitt,D; Halls,JJM; Heeney,H; de,Mello JC (Advanced Functional Materials, 2012)
A method is reported for the controlled synthesis of device-grade semiconducting polymers, utilizing a droplet-based microfluidic reactor. Using poly(3-hexylthiophene) (P3HT) as a test material, the reactor is shown to provide a controlled and stable environment for polymer synthesis, enabling control of molecular weight via tuning of flow conditions, reagent composition or temperature. Molecular weights of up to 92 000 Da are readily attainable, without leakage or reactor fouling. The method avoids the usual deterioration in materials quality that occurs when conventional batch syntheses are scaled from the sub-gram level to higher quantities, with a prototype five-channel reactor producing material of consistent molecular weight distribution and high regioregularity (>98%) at a rate of ≈60 g/day. The droplet-synthesized P3HT compares favorably with commercial material in terms of absorption spectrum, polydispersity, regioregularity, and crystallinity, yielding power conversion efficiencies of up to 4% in bulk heterojunction solar cells with [6,6]-phenyl-C61-butyric acid methyl ester.